Reimagining Community Empowerment: Integrating Digital Technology, Social Innovation, and Cultural Sustainability - Zeynep Toprak; Cemil Kaya; Hale Yilmaz; Guntur Arie Wibowo (Pengabdian: Jurnal Abdimas, 2026)
Background: Community empowerment has become increasingly complex in the context of rapid digital transformation, evolving social challenges, and the growing urgency of cultural sustainability. Conventional empowerment models often treat digital technology, social innovation, and culture as separate domains, limiting their capacity to respond holistically to contemporary community needs. Objective: This study aims to reimagine community empowerment by examining how digital technology, social innovation, and cultural sustainability can be integrated into a coherent and mutually reinforcing framework. Methods: The research employed a qualitative-dominant design supported by descriptive and inferential analysis. Data were collected through interviews, observations, document analysis, and secondary program data involving community members, local leaders, and innovation facilitators. Results: The findings indicate that communities achieve stronger empowerment outcomes when digital tools are embedded within socially driven innovation and aligned with local cultural values. Integrated practices enhance participation, collective agency, innovation capacity, and cultural continuity, while technology-centered approaches alone produce limited and uneven outcomes. Conclusion: The study concludes that sustainable community empowerment requires an integrative approach in which digital technology functions as an enabling instrument, social innovation acts as a transformative mechanism, and cultural sustainability provides normative grounding. This model offers a holistic pathway for inclusive and resilient community development.